Knowledge and perceptions of the COVID‐19 pandemic among patients with myasthenia gravis. Issue 3 (20th December 2020) - Li, Yingkai; Emmett, C. Douglas; Cobbaert, Marjan; Sanders, Donald B.; Juel, Vern C.; Hobson‐Webb, Lisa D.; Massey, Janice M.; Gable, Karissa L.; Raja, Shruti M.; Gonzalez, Natalia L.; Guptill, Jeffrey T.
Abstract: Background: Patients with myasthenia gravis (MG) may be particularly vulnerable during the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic due to risk of worsening disease during infection, potential adverse impacts of coronavirus disease 2019 (COVID‐19) treatments on neuromuscular transmission, and a limited ability to fight off infection related to immunosuppressive treatments. Our goal is to understand how patients are experiencing the COVID‐19 pandemic, including where they receive relevant information, how it has affected medical care, and what measures they use to protect themselves. Methods: This is a prospective online survey study at large academic practice. All patients with a neuromuscular junction disorder diagnosis code in the Duke Health System were invited to participate. Results: One thousand eight hundred and forty eight patients were approached to participate and 75 completed the survey between 16 April 2020 and 28 May 2020. The most frequently used information sources were non‐presidential federal government (75%), state government (57%), local healthcare provider (37%), and television news (36%). Non‐presidential federal government (80%), local healthcare providers (55%), state government (33%), and patient support organizations (29%) were considered the most trusted information sources. Thirty‐three (44%) of survey responders had attended a telemedicine visit. Patients were taking recommended precautions during the pandemic and remained very concerned (69%) about COVID‐19. Generalized Anxiety Disorder‐7 scores were moderate‐severe in 20% of responders. Conclusions: Healthcare providers, the government, and patient organizations play a critical role in communicating with the MG patient community. Use of targeted messaging strategies by these groups to convey accurate information may increase effectiveness and lead to more informed patients with reduced anxiety.